Art or Science? Measuring the Impact of Business Environment Reforms at the Subnational Level - Thomas, Margo; Cordova-Novion, Cesar; Batic, Ana (World Bank, Washington, DC, 2012)
As the Western Balkan economies look toward integration into the European Union, each is striving to increase its competitiveness and improve its economic growth. Considerable momentum has been developing on business enabling environment (BEE) reform. The overall doing business rankings for the countries in this region are in the third and fourth quartiles for 2009, showing plenty of room for improvement. Investors identified improvements in regulations affecting businesses as a key priority for upgrading the business enabling environment in the region. In this smart lesson, the author shares the experience of adapting the standard cost model to review regulations and measure impact in supporting BEE reforms at the subnational level in Bosnia and Herzegovina, Montenegro, and Serbia. The authors have adapted a relatively sophisticated tool, and applied it to support BEE reforms to: (1) measure the impact of the reforms in terms of cost savings for businesses; (2) help drive the reform agenda by enabling policymakers to build stakeholder support and target reforms recognizing that 'what gets measured, gets done'; and (3) support the regional monitoring and evaluation framework.